Analysis of Student Ability in Solving PISA-Like Math Problems: a case study in SMPN 8 Banda Aceh, Indonesia (International Journal of Scientific Research and Management (IJSRM), 2018)
The Programme International for Student Assessment (PISA) has become a tool in determining the quality of education in a certain country. Unfortunately, Indonesian students still have difficulties in solving PISA problems. In an effort to improve students’ ability in Indonesia to solve PISA questions, we need to analyze their difficulties in solving contextual problems. In this study, we have developed PISA-like problems by taking into account the contextual environment of students and current Indonesian curriculum. Forty-eight PISA-like math problems in Bahasa Indonesia have been developed consisting of sixteen questions level one, sixteen questions level two, and sixteen questions level three. Then, those PISA-like math problems were used to assess the students’ ability (case study in SMPN 8 Banda Aceh, Indonesia). Our study revealed that the ability of students is very low in understanding the information given in the problems. The students’ ability in the mathematical process and decoding are also quite low. Students should practice the PISA-like problems in the teaching-learning process in order to improve their abilities in PISA.